Genetic variability of the pear lace bug Stephanitis pyri F. (Heteroptera: Tingidae) in Krasnodar Territory, Russia - E. N. Besedinа; V. I. Kil (Юг России: экология, развитие, 2023)
Aim. Study of the genetic variability of the pear lace bug Stephanitis pyri F. depending on geographical location and trophic specialization.Material and Methods. The object of the study was insect samples (n=60) from the natural population of the pear lace bug Stephanitis pyri F. (Tingidae: Heteroptera) in the Krasnodar Territory: in Krasnodar, Kropotkin and Novorossiysk. The collection of S. pyri bugs was carried out on model trees of domestic apple (Malus domestica Borkh) and sour cherry (Prunus cerasus L.). Molecular genetic analysis was carried out in several stages: sample preparation, DNA extraction, and diagnostics based on RAPD (random amplified polymorphic DNA)‐PCR (DNA amplification).Results. With the help of molecular genetic markers, the genetic variability of the pear lace bug in the Krasnodar Territory was studied. The indicators of genetic differentiation between geographic (Gst=0.209) and trophic (Gst=0.049–0.302) intrapopulation groups of S. pyri were calculated. The levels of variability were determined within geographic (79.1 %) and trophic groups (70.0–95.1 %), as well as between them – 20.9 % and 4.9–30 %, respectively. The influence of the food factor on the genetic diversity and differentiation of insect populations is shown through the example of the Kropotkin trophic group of bugs that prefer the sour cherry P. cerasus as the main food plant.Conclusion. A small effect of isolation by distance was noted, which was characterized by a weak dependence of geographical and genetic distances between the population groups of the pear lace bug. The influence of the nutritional factor on the genetic variability of phytophages populations has been established, as is confirmed by other researchers.